Enhancing the Selectivity and Confinement of the Cu(II)‐Mediated Chan‐Lam Coupling for Use in Building Point‐of‐Care Diagnostics - Chang, Yu‐Chia; Moeller, Kevin D. (ChemElectroChem, 2025)
The Cu(II)‐mediated Chan‐Lam coupling reaction offers several benefits for developing point‐of‐care detection devices on microelectrode arrays. However, achieving selectivity on borate ester‐based polymer surfaces has proven difficult due to background reactions. Fluorescence‐based studies were conducted using fluorescently labeled acetylene nucleophiles. Initial experiments revealed significant background fluorescence across the electrode array, indicating selectivity issues. Further investigation uncovered significant background reactions occurring even without copper. To address this, a strategy utilizing an arylbromide‐based polymer was developed, enhancing reaction selectivity by minimizing background non‐specific reactions. Exploration into the confinement mechanism revealed the role of acetylene in forming dimers, facilitating rapid consumption of Cu(II) reagents that escaped from the specific electrodes used. These findings offer a way to construct devices for the multiplex point‐of‐care detection of metabolites, improving performance and accuracy in diagnostic devices.